Amusement Industry and Lean Six Sigma - Lavrenov, Tymur; Martínez, Felipe; Rathouský, Bedřich; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis applies the Lean Six Sigma DMAIC framework to the order assembly and packing process in the warehouse of Netronic Europe, a distributor of laser tag equipment. The aim is to reduce order processing time and increase the share of orders completed correctly at the first attempt. The process is mapped, Critical-to-Quality indicators are defined, and time-based data are analysed to identify the main sources of delay and rework. On this basis, a set of low- cost improvements and a simple control plan are proposed, tailored to a single-operator warehouse environment. The thesis provides practical guidance for stabilising a key internal process in a small entertainment supplier and contributes an additional case of Lean Six Sigma application in a niche, service-related logistics setting.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses